Role of PKM2-Mediated Immunometabolic Reprogramming on Development of Cytokine Storm - Liu, Zhijun; Le, Yifei; Chen, Hang; Zhu, Ji; Lu, Dezhao (Frontiers in Immunology, 2021)
The cytokine storm is a marker of numerous illness (including COVID-19) severity and increased mortality. The altered metabolic profile and energy generation of immune cells affect their activation, exacerbating the cytokine storm. Immunometabolism is an emerging field that highlights the importance of specific metabolic pathways in immune regulation. The glycolytic enzyme pyruvate kinase M2 (PKM2) is a key regulator of immunometabolism and bridges metabolic and inflammatory dysfunction. It can alter its conformation thus walking in different fields including metabolism and inflammation and associate with various transcription factors. This review explored the vital role of PKM2 in mediating immunometabolic reprogramming and its role in inducing cytokine storm, with a focus on providing references for further understanding of its pathological functions and for proposing new targets for the treatment of related diseases.